서울시 50대 정신건강검진사업에 대한 웹기반 조사 - 안승민; 이미경; 이소희; 석정호; 이해우; 강석훈; 백종우; An, Seung-Min; Lee, Mikyung; Lee, So Hee; Seok, Jeong-Ho; Lee, Haewoo; et al. (Anxiety and mood, 2017)
Objective : A pilot project entitled '50s mental health screening project' was conducted in Seoul. As a part of this project, we conducted surveys to obtain the opinions of psychiatrists regarding mental health screenings. Methods : A questionnaire was mailed to members registered with the Korean Neuropsychiatric Association, which enquired about the '50s mental health screening project'. Results: A majority (90.9%) of the subjects agreed on the purpose and implementation of the project. However, there were fewer individuals that actually showed the intent to participate (65.8%). The mean age of the group with the intention to participate was higher compared to the group with no intention to participate. The factors that negatively affected the intent to participate included prejudice and discrimination against psychiatry (3.795), low health insurance reimbursement (3.784), and inconvenience of reporting to public health centers (3.664). The most appropriate method that scored the highest for screening mental health was face-to-face consultation with a psychiatrist (3.889). Most of the participants agreed on the method of a self-reported survey along with an interview of psychiatrist (84.9%). Conclusion : Subjects were concerned about prejudice and discrimination against psychiatry, low health insurance reimbursement, and inconvenience of reporting to public health centers. These problems need to be supplemented. Face-to-face consultation with a psychiatrist may be considered an appropriate method for future mental health screening.